Immunoepidemiology of Wuchereria bancrofti infection: Parasite transmission intensity, Filaria-specific antibodies, and host immunity in two East African communities - Jaoko, Walter G.; Michael, Edwin; Meyrowitsch, Dan W.; Estambale, Benson B.; Malecela, Mwele N.; Simonsen, Paul E. (American Society for Microbiology, 2007)
We compared the age profiles of infection and specific antibody intensities in two communities with different transmission levels in East Africa to examine the contribution of humoral responses to human immunity to the vector-borne helminth Wuchereria bancrofti. The worm intensities were higher and exhibited a nonlinear age pattern in a high-transmission community, Masaika, in contrast to the low but linearly increasing age infection profile observed for a low-transmission community, Kingwede. The mean levels of specific immunoglobulin G1 (IgG1), IgG2, IgG4, and IgE were also higher in Masaika, but intriguingly, the IgG3 response was higher in Kingwede. The age-antibody patterns differed in the two communities but in a manner apparently contrary to a role in acquired immunity when the data were assessed using simple correlation methods. By contrast, multivariate analyses showed that the antibody response to infection may be classified into three types and that two of these types, a IgG3-type response and a response measuring a trade-off in host production of IgG4 and IgG3 versus production of IgG1, IgG2, and IgE, had a negative effect on Wuchereria circulating antigen levels in a manner that supported a role for these responses in the generation of acquired immunity to infection. Mathematical modeling supported the conclusions drawn from empirical data analyses that variations in both transmission and worm intensity can explain community differences in the age profiles and impacts of these antibody response types. This study showed that parasite-specific antibody responses may be associated with the generation of acquired immunity to human filarial infection but in a form which is dependent on worm transmission intensity and interactions between immune components.